Chemically toughened microcrystalline glass, preparation method, and application thereof
By forming a compressive stress layer of specific depths and strengths on the glass surface, and combining thermal bending treatment, the problem of insufficient impact resistance and durability of glass materials is solved, and glass materials with high strength and high optical properties are achieved.
Patent Information
- Application Number
- JP2024186257
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-07-08
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2042-04-28
AI Technical Summary
Existing glass materials have shortcomings in impact resistance and durability, especially in high-pressure environments, which are prone to fragmentation, making it difficult to meet the high requirements of electronic products for glass materials.
By forming a NA/LI exchange layer and a K/NA exchange layer on the glass surface, the depth and strength of the compressive stress layer are controlled, and combined with thermal bending treatment, the glass is improved with the compression stress and crack resistance.
It significantly improves the impact resistance and crack resistance of glass, enhances the durability and optical properties of glass, and is suitable for electronic devices in various structural forms.
Smart Images

Figure 2025016546000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims priority to Chinese Patent Application No. 202110774451.0, filed with the State Intellectual Property Office of China on July 8, 2021, entitled "Chemically Strengthened Microcrystalline Glass, Preparation Method and Application Thereof," which is incorporated herein by reference in its entirety.
[0002] This application relates to the field of glass product technology, and in particular to chemically strengthened microcrystalline glasses and preparation methods and applications thereof. [Background technology]
[0003] Glass is widely used in daily life due to its properties such as transparency and high temperature resistance. For example, glass is widely used in protective equipment field, decoration field and other fields. However, glass also has some disadvantages such as weak impact resistance and fragility, which limits the application of glass in some fields.
[0004] With the popularity of electronic products, the requirements imposed on glass materials are becoming higher and higher. For example, the screen protection materials of most of the current smartphones are chemically strengthened glass materials. In addition, with the development of electronic products, the back cover materials of electronic products are gradually replaced by glass and other materials.
[0005] At present, the cover glass material in the industry has developed from primary tempered aluminosilicate glass to secondary tempered lithium aluminosilicate glass. As the degree of chemical tempering increases, the perforation resistance of the cover to rough ground is effectively improved. In order to achieve generational improvement in the grit sandpaper drop test, from 2016 to 2021, the iterative direction of secondary tempered glass in the industry has developed toward increased deep stress.
[0006] However, in practical applications, the following shortcomings have been found in the cover glass material and other aluminosilicate glasses in the industry:
[0007] The body of the secondary tempered glass uses lithium aluminosilicate glass, and the Young's modulus of lithium aluminosilicate glass is usually about 80 GPa. Further improvement of the stress strength of lithium aluminosilicate glass is limited by the compressive stress accumulation capacity of the substrate. Excessive compressive stress leads to high internal tensile stress. If the tensile stress is too high, the ineffective glass fragments will be too small (less than 3 mm) or the cover glass will suddenly explode. Therefore, the improvement of the mechanical strength of the secondary tempered glass is limited by the restriction on the stress strength caused by the body strength, and the improvement of the drop resistance is relatively limited.
[0008] Since 2020, the cover industry has publicized microcrystalline glass as a new development direction for cover glass. The nanocrystals in microcrystalline glass can resist cracks and punctures, and the compressive stress brought about by ion exchange can resist crack growth. These two features can improve the drop resistance of cover glass (see Figure 1 for the mechanism). Therefore, the drop resistance of microcrystalline glass on rough ground is greatly improved compared with secondary tempered glass.
[0009] For example, the main crystalline phases of the disclosed type of microcrystalline glass are petalite and lithium disilicate. Li2O needs to be actively introduced into the strengthening boiler water of the microcrystalline glass to control the concentration of sodium salts on the surface, thereby reducing the degree of precipitation of sodium salts at a temperature of 85°C and a humidity of 85%. This crystalline phase design implements the increase in strength through two exchanges, namely K / Na exchange and Na / Li exchange. However, research has shown that microcrystalline glass is characterized by the need for a relatively high degree of crystallinity (85wt% or more) to ensure the excellent optical performance of the raw material (transmittance of 89.5% or more, absolute value of chromatic aberration b of 0.5 or less, haze of 0.15% or less). However, in the three-dimensional hot bending forming process, the crystalline phase of this type of microcrystalline glass is easily affected by heat, and the optical performance is always deteriorated. In addition, the ion exchange of the microcrystalline glass is affected by the crystalline phase and requires a longer exchange path. Therefore, it is difficult to obtain a relatively high compressive stress by chemical strengthening, and the improvement in drop resistance is still insufficient. Summary of the Invention
[0010] The purpose of the present application is to overcome the shortcomings of the prior art and provide a chemically strengthened microcrystalline glass and a preparation method and its application, thereby solving the technical problems that it is difficult to further increase the compressive stress of existing aluminosilicate glass and existing chemically strengthened microcrystalline glass, and that their drop resistance is insufficient.
[0011] In order to achieve the above-mentioned object of the application, according to one aspect of the embodiment of the present application, a chemically strengthened microcrystalline glass is provided. In this embodiment of the present application, the chemically strengthened microcrystalline glass has a Na / Li exchange layer, and the depth Doc of the compressive stress layer of the chemically strengthened microcrystalline glass is 0.15t to 0.22t. The compressive stress intensity CS50 of the strengthening depth of 50 μm in the surface layer of the chemically strengthened microcrystalline glass is 130 + (20t-13) × 15 MPa to 230 + (20t-13) × 15 MPa. CS50 and Doc satisfy CS50 / (Doc-50) is 1.4 to 6 (MPa / μm unit), and t is the overall thickness of the chemically strengthened microcrystalline glass.
[0012] The chemically strengthened microcrystalline glass in this embodiment of the present application has a specific depth of the compressive stress layer, a specific compressive stress intensity, and a relationship between the depth of the compressive stress layer and the compressive stress intensity. The chemically strengthened microcrystalline glass is given a relatively high compressive stress and a much higher stress intensity than the existing aluminosilicate glass and microcrystalline glass, and therefore can resist crack growth. Therefore, in this embodiment of the present application, the perforation resistance of the chemically strengthened microcrystalline glass against rough ground is significantly improved, and the drop height using rough ground is higher than that of the existing aluminosilicate glass and microcrystalline glass.
[0013] Optionally, when the chemically strengthened microcrystalline glass is pressed and crushed by a metal compression rod with a 10 mm diameter round head, the average size of the longest side of the fragments is 5 mm or more.
[0014] Optionally, when the thickness is 0.6 mm, the grit sandpaper drop test height of the chemically strengthened microcrystalline glass is 1.5 m or more.
[0015] Optionally, no sodium salts precipitate on an outer surface of the chemically strengthened microcrystalline glass when the chemically strengthened microcrystalline glass is stored in an environment at a temperature of 85° C. and a humidity of 85% for 72 hours.
[0016] Optionally, when the thickness of the chemically strengthened microcrystalline glass is 0.8 mm or less, the average transmittance of light with a wavelength of 400 nm to 940 nm is 89.5% or more, the difference in single-point transmittance between a wavelength of 550 nm and a wavelength of 400 nm is less than 1%, the absolute value of the color coordinate b is 0.4 or less, and the haze is 0.15% or less.
[0017] Based on the depth of the compressive stress layer, the compressive stress intensity, and the relationship between the depth of the compressive stress layer and the compressive stress intensity, the chemically strengthened microcrystalline glass has excellent puncture resistance against rough ground, high drop resistance, and excellent thermal stability and moisture resistance.In addition, the chemically strengthened microcrystalline glass has excellent optical performance, such as excellent light transmittance.
[0018] Optionally, the main crystalline phase of the raw microcrystalline glass used to form the chemically strengthened microcrystalline glass is either lithium metasilicate or β-quartz solid solution, the mass fraction of the total contained crystalline phase is 35%-75%, and the total content of the secondary crystalline phase is less than 5%. Through the control of the type of the main crystalline phase of the raw microcrystalline glass and the content of each crystalline phase, the Na / Li exchange layer contained in the chemically strengthened microcrystalline glass can be effectively prevented from being adversely affected by Li, and the CS50 range can be effectively controlled, thereby further improving the drilling resistance of the chemically strengthened microcrystalline glass against rough ground. In addition, the impact resistance and optical performance such as light transmittance of the chemically strengthened microcrystalline glass can be improved.
[0019] Furthermore, the raw microcrystalline glass includes main components and nucleating agents. The main components include SiO2, Al2O3, B2O3, Li2O, Na2O, and K2O, and the content of SiO2+Al2O3+B2O3 is 58-85 mol%, and the content of Li2O+Na2O+K2O is 10-32 mol%. The nucleating agents include TiO2, P2O5, and ZrO2, and the content of TiO2+P2O5+ZrO2 is 2-8 mol%. These components of the raw microcrystalline glass provide the raw microcrystalline glass and the chemically strengthened microcrystalline glass with the above types of main crystal phases and the content of each crystal phase, thereby improving the drilling resistance of the chemically strengthened microcrystalline glass to rough ground and improving the optical performance such as light transmittance of the chemically strengthened microcrystalline glass.
[0020] Furthermore, the glass matrix of the original microcrystalline glass is prepared by using a melting and casting method or a calendaring method.
[0021] Furthermore, the glass matrix of the original microcrystalline glass is heat treated in two stages: Heat treatment stage 1: Temperature is 500℃~600℃, treatment time is 0.1 hours~10 hours Heat treatment stage 2: The temperature is 640℃~800℃, and the treatment time is 0.1 hours~10 hours.
[0022] A two-step heat treatment is carried out on the glass matrix of the raw microcrystalline glass, so that the raw microcrystalline glass formed can obtain the required main crystalline phase and the content of the main crystalline phase, and adjust other secondary crystalline phases, thereby improving the drilling resistance and optical performance of the chemically strengthened microcrystalline glass against rough ground.
[0023] In addition, the Young's modulus of the chemically strengthened microcrystalline glass is 95 GPa or more. Based on the type of main crystal phase of the chemically strengthened microcrystalline glass and the content of each crystal phase of the original microcrystalline glass, the chemically strengthened microcrystalline glass is endowed with a high Young's modulus, so that the chemically strengthened microcrystalline glass is endowed with a storage capacity for larger compressive stress, providing conditions for increasing the compressive stress of the chemically strengthened microcrystalline glass.
[0024] Optionally, the surface layer of the chemically strengthened microcrystalline glass further comprises a K / Na exchange layer. The introduction of the K / Na exchange layer (potassium layer) further improves the impact resistance of the chemically strengthened microcrystalline glass and helps the chemically strengthened microcrystalline glass maintain its resistance to being dropped on rough ground.
[0025] Furthermore, the thickness of the K / Na exchange layer is less than 3 μm. Through the control of the thickness of the K / Na exchange layer (potassium layer), the impact resistance and drop resistance on rough ground of the chemically strengthened microcrystalline glass can be further improved. Based on the depth of the compressive stress layer, the compressive stress intensity, and the relationship between the depth of the compressive stress layer and the compressive stress intensity, the requirement for the thickness of the K / Na exchange layer can be effectively reduced.
[0026] Optionally, the chemically strengthened microcrystalline glass is any one of chemically strengthened microcrystalline glass with a two-dimensional structure, chemically strengthened microcrystalline glass with a 2.5-dimensional structure, or chemically strengthened microcrystalline glass with a three-dimensional structure. Since the chemically strengthened microcrystalline glass has excellent drilling resistance and optical performance against rough ground as described above, the chemically strengthened microcrystalline glass can be any one of chemically strengthened microcrystalline glass with a two-dimensional structure, chemically strengthened microcrystalline glass with a 2.5-dimensional structure, or chemically strengthened microcrystalline glass with a three-dimensional structure. This expands the application range of the chemically strengthened microcrystalline glass and improves the quality and performance stability of the corresponding products.
[0027] Furthermore, when the chemically strengthened microcrystalline glass is chemically strengthened microcrystalline glass with a two-dimensional structure and / or chemically strengthened microcrystalline glass with a 2.5-dimensional structure, the absolute value of the color coordinate b is 0.3 or less, and the haze is 0.14% or less for the chemically strengthened microcrystalline glass with a two-dimensional structure and / or the chemically strengthened microcrystalline glass with a 2.5-dimensional structure.
[0028] When the chemically strengthened microcrystalline glass is a chemically strengthened microcrystalline glass having a two-dimensional structure, or when the chemically strengthened microcrystalline glass is a chemically strengthened microcrystalline glass having a 2.5-dimensional structure, the chemically strengthened microcrystalline glass has excellent perforation resistance against rough ground and excellent light transmittance.
[0029] Furthermore, when the chemically strengthened microcrystalline glass has a three-dimensional structure, the long side bending angle of the chemically strengthened microcrystalline glass having a three-dimensional structure is 15° to 89°.
[0030] Furthermore, for the chemically strengthened microcrystalline glass having a three-dimensional structure, the absolute value of the color coordinate b is 0.4 or less, and the haze is 0.15% or less.
[0031] As a three-dimensional structured chemically strengthened microcrystalline glass, the chemically strengthened microcrystalline glass still has excellent puncture resistance to rough ground and excellent light transmittance.
[0032] According to another aspect of the present embodiment, there is provided a method for preparing the chemically strengthened microcrystalline glass of the above-mentioned embodiment of the present application, which comprises the steps of: performing a primary chemical strengthening treatment on the raw microcrystalline glass to be subjected to the chemical strengthening treatment in a sodium salt-containing bath to form a Na / Li exchange layer.
[0033] According to the preparation method of chemically strengthened microcrystalline glass in the present application, a primary chemical strengthening treatment is carried out on the raw microcrystalline glass in a sodium salt-containing bath, so that a Na / Li exchange layer is formed on the surface layer of the raw microcrystalline glass. In addition, through control of the primary chemical strengthening treatment, the chemically strengthened microcrystalline glass formed by chemical strengthening can have the depth of the compressive stress layer, the compressive stress intensity CS50 range, and the relationship of the chemically strengthened microcrystalline glass in the above-mentioned embodiment of the present application. In this way, the prepared chemically strengthened microcrystalline glass is endowed with a relatively high compressive stress and a greatly improved stress intensity, can withstand crack growth, and has excellent perforation resistance to rough ground. In addition, in the present application, the chemical strengthening conditions for the preparation method of chemically strengthened microcrystalline glass in the present application are easy to control, so that the prepared chemically strengthened microcrystalline glass has stable performance, high efficiency, and reduced preparation cost.
[0034] Optionally, the sodium-containing salt bath comprises NaNO3 or a salt mixture of NaNO3 and KNO3, in which the NaNO3 content is 50 wt% or more.
[0035] Optionally, in the first chemical strengthening treatment, the temperature is 380°C to 450°C, and the strengthening time is 0.5 hours to 6 hours.
[0036] Through controlling the type of sodium-containing salt bath, the content of NaNO3, and the primary chemical strengthening treatment, the effect of the chemical strengthening treatment on the raw microcrystalline glass is improved, and the depth of the compressive stress layer and the compressive stress intensity CS50 range of the formed chemically strengthened microcrystalline glass are optimized, so that the compressive stress of the chemically strengthened microcrystalline glass is increased, and the perforation resistance and light transmittance performance of the chemically strengthened microcrystalline glass on rough ground are improved.
[0037] Optionally, after the primary chemical strengthening treatment, the method further comprises performing a secondary chemical strengthening treatment on the chemically strengthened microcrystalline glass on which the Na / Li exchange layer has been formed in a potassium salt-containing bath to form a K / Na exchange layer. By further performing a secondary chemical strengthening treatment on the chemically strengthened microcrystalline glass formed by the primary chemical strengthening treatment, a K / Na exchange layer is formed on the surface layer of the formed chemically strengthened microcrystalline glass, so that the impact resistance and drop resistance against rough ground of the chemically strengthened microcrystalline glass are further improved.
[0038] Further, the potassium-containing salt bath contains KNO3 or a salt mixture of NaNO3 and KNO3, in which the content of KNO3 is 80 wt% or more.
[0039] Furthermore, in the secondary chemical strengthening treatment, the temperature is 380° C. to 450° C., and the strengthening time is 0.2 to 1 hour.
[0040] Through controlling the type of potassium-containing salt bath, the content of KNO3, and the secondary chemical strengthening treatment, the effect of the secondary chemical strengthening treatment is improved, and the impact resistance and drop resistance on rough ground of the chemically strengthened microcrystalline glass are further improved.
[0041] Optionally, before performing a primary chemical strengthening treatment on the raw microcrystalline glass that is the subject of the chemical strengthening treatment in a sodium salt-containing bath, the method further comprises performing the following hot bending treatment on the raw microcrystalline glass.
[0042] The hot bending process is carried out on the raw microcrystalline glass at 650° C. to 750° C. to form a three-dimensional raw microcrystalline glass. The time of each hot bending process is 30 seconds to 120 seconds, and the pressure of the hot bending process is 0.1 MPa to 0.9 MPa.
[0043] The three-dimensional raw microcrystalline glass is formed by carrying out a hot bending process on the raw microcrystalline glass, so that after a primary chemical strengthening process or a further secondary chemical strengthening process, a chemically strengthened microcrystalline glass having a three-dimensional structure can be formed, ensuring that the chemically strengthened microcrystalline glass having a three-dimensional structure has high compressive stress, excellent puncture resistance against rough ground, and excellent light transmittance performance.
[0044] According to another aspect of the embodiment of the present application, an electronic device is provided. In the present embodiment of the present application, the electronic device includes a glass component, and the glass component is the chemically strengthened microcrystalline glass in the above embodiment of the present application, or the chemically strengthened microcrystalline glass prepared by using the preparation method of the chemically strengthened microcrystalline glass in the above embodiment of the present application. The chemically strengthened microcrystalline glass in the present embodiment of the present application has excellent perforation resistance and optical performance against the rough ground described above, or further has excellent impact resistance. Therefore, the glass component is endowed with excellent drop resistance and impact resistance, as well as high strength. In this way, the electronic device in the present embodiment of the present application is endowed with excellent drop resistance and impact resistance, as well as impact resistance, and the quality and operational performance stability of the electronic device are high.
[0045] Furthermore, the glass component includes at least one of a display cover, a protective cover, or a protective screen. The glass component has excellent light transmission, strong protection, and drop and crash resistance, and also has high strength, excellent display performance, and stability. [Brief description of the drawings]
[0046] [Figure 1] FIG. 1 is a schematic diagram of the perforation resistance mechanism of crystallized glass.
[0047] [Diagram 2] FIG. 2 is a diagram of stress curves for an existing primarily strengthened aluminosilicate glass, an existing secondarily strengthened lithium aluminosilicate glass, and a chemically strengthened microcrystalline glass, according to embodiments of the present application.
[0048] [Diagram 3] 1 is a schematic flow chart of a method for preparing a chemically strengthened microcrystalline glass, according to an embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0049] In order to make the technical problem to be solved, the technical solution and the advantageous effects of the present application clearer, the present application will be further described in detail below with reference to the embodiments. It should be understood that the specific embodiments described in this specification are merely used to explain the present application, and are not used to limit the present application.
[0050] In the present description, the term "and / or" is understood to describe a correspondence between related objects and represents three possible relationships. For example, A and / or B may represent three cases: only A is present, both A and B are present, and only B is present. A and B may be singular or plural. The character " / " generally represents an "or" relationship between related objects.
[0051] As used herein, "at least one" means one or more, and "multiple" means two or more. "At least one of the following items" or similar expressions means a single item or any combination of those items, including any combination of multiple items. For example, "at least one of a, b, or c" or "at least one of a, b, and c" can both refer to a, b, c, ab (i.e., a and b), ac, bc, or abc, where there can be one or more of a, b, and c.
[0052] The terms used in the embodiments of the present application are merely used for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular terms "a," "the," and "said" used in the embodiments of the present application and the appended claims are also intended to include the plural forms unless the context clearly dictates otherwise.
[0053] In the present application, the term "and / or" describes a correspondence between related objects and indicates that three relationships may exist. For example, A and / or B may indicate three cases: only A is present, both A and B are present, and only B is present. A and B may be singular or plural. The character " / " generally indicates an "or" relationship between related objects.
[0054] It should be understood that in various embodiments of the present application, the sequence numbers of each of the above processes do not imply the order of execution. Some or all of the steps may be executed in parallel or may be executed in sequence. The order of executing the processes should be determined based on the functions and internal logic of the processes, and no limitations may be imposed on the implementation process of the embodiments of the present application.
[0055] The weight of the relevant component mentioned in the specification of the embodiment of the present application may not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, even if the weight of the relevant component is proportionally scaled up or down according to the content of the relevant component in the specification of the embodiment of the present application, the weight of the relevant component still belongs to the range disclosed in the specification of the embodiment of the present application. Specifically, the mass described in the specification of the embodiment of the present application may be a mass unit well known in the chemical engineering field, such as μg, mg, g, or kg.
[0056] The terms "first" and "second" are used only for descriptive purposes to distinguish objects, such as substances, from one another, and cannot be understood as indicating or implying the relative importance or quantity of the technical features depicted. For example, "firstXX" may also be referred to as "secondXX" and similarly, "secondXX" may also be referred to as "firstXX" without departing from the scope of the embodiments of the present application. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features.
[0057] Below is an explanation of the specific names involved.
[0058] Raw microcrystalline glass: Unstrengthened microcrystalline glass.
[0059] Chemically strengthened microcrystalline glass: Chemically tempered microcrystalline glass processed by using high temperature ion exchange process. In high temperature molten salt, large alkali metal ions replace small alkali metal ions in glass, generating a volume difference between the exchanged ions, generating high and low compressive stresses in the surface layer of the original glass, thereby achieving the purpose of preventing and delaying the propagation of small cracks in glass and improving the mechanical strength of glass.
[0060] Depth of compressive stress layer (Doc): Depth of compressive stress layer in chemically strengthened microcrystalline glass.
[0061] Compressive stress value at a depth of 50 μm in the surface layer of chemically strengthened microcrystalline glass (CS50): represents the compressive stress value at a depth of 50 μm in the surface layer of chemically strengthened microcrystalline glass.
[0062] Na / Li exchange layer: refers to a sodium-containing layer in chemically strengthened microcrystalline glass in which some lithium ions have been replaced by sodium ions.
[0063] K / Na-Exchanged Layer: Refers to a potassium-containing layer in chemically strengthened microcrystalline glass in which some sodium ions have been replaced by potassium ions.
[0064] Sodium-Lithium Ion Exchange: In chemical strengthening, sodium ions in a salt bath replace lithium ions in the glass.
[0065] Potassium-sodium ion exchange: In chemical strengthening, potassium ions in the salt bath replace sodium ions in the glass.
[0066] According to one aspect, an embodiment of the present application provides a chemically strengthened microcrystalline glass. In this embodiment of the present application, the chemically strengthened microcrystalline glass has a Na / Li exchange layer and a compressive stress layer. Measurement results show that the stress curve of the chemically strengthened microcrystalline glass in this embodiment of the present application is shown in Figure 2, and the depth and compressive stress intensity of the compressive stress layer of the chemically strengthened microcrystalline glass have at least the following characteristics 1 to 3.
[0067] 1. The depth Doc of the compressive stress layer of the chemically strengthened microcrystalline glass and the overall thickness of the chemically strengthened microcrystalline glass satisfy the relationship shown in the following formula 1-1. Doc=0.15t~0.22t Formula (1-1)
[0068] 2. The compressive stress intensity in the surface layer of the chemically strengthened microcrystalline glass satisfies the relationship shown in the following formula 1-2.
[0069] The compressive stress strength CS50 at a strengthening depth of 50 μm in the surface layer of the chemically strengthened microcrystalline glass satisfies the relationship shown in the following formula 1-2. CS50=130+(20t-13)×15Mpa~230+(20t-13)×15MPa Formula (1-2)
[0070] 3. The relationship between the compressive stress intensity in the surface layer of the chemically strengthened microcrystalline glass and the depth of the compressive stress layer, Doc, satisfies the following formula 1-3. CS50 / (Doc-50)=1.4~6, unit MPa / μm Formula (1-3)
[0071] In formula 1-1 and formula 1-2, t is the overall thickness of the chemically strengthened microcrystalline glass. Therefore, t is a positive number greater than 0, and the unit of t may be mm. In this embodiment, t, i.e., the overall thickness of the chemically strengthened microcrystalline glass in this embodiment of the present application, is 0.3 mm to 0.8 mm.
[0072] The strengthening depth of 50 μm in the surface layer in formula 1-2 refers to the area at an internal depth of 50 μm in the direction from the surface of the chemically strengthened microcrystalline glass to the inside. In the process of experiment, it was found that when the CS50 of the chemically strengthened microcrystalline glass in this embodiment of the present application is too low, the ability of the chemically strengthened microcrystalline glass, such as the drilling resistance against rough ground, is reduced, and reliability is affected. When the CS50 is too high, the broken pieces of the chemically strengthened microcrystalline glass become too small.
[0073] In addition, in the existing primary strengthened aluminosilicate glass shown in Figure 2 (main components: SiO2+Al2O3+B2O3+P2O5=75-85mol%, Na2O+K2O=10-16mol%, no Li2O, in the tempering process of this glass, pure KNO3 is usually used to temper at 380℃-460℃ for 1h-10h), the CS of the primary strengthened aluminosilicate glass is above 700MPa, the CS50 is almost equal to 0, and the depth of the strengthening layer (i.e., K / Na exchange layer) is 0.04t-0.09t. In the existing secondary strengthened lithium aluminosilicate glass (main components: SiO2+Al2O3+B2O3+P2O5=75~85mol%, Li2O+Na2O+K2O=10~20mol%, secondary strengthening process is usually used, pure NaNO3 or NaNO3 / KNO3 salt mixture is used for primary strengthening, the strengthening temperature is 380℃~450℃, pure KNO3 or NaNO3 / KNO3 salt mixture is used for secondary strengthening), the CS of secondary strengthened lithium aluminosilicate glass is more than 700MPa, the strengthening depth Dol of potassium layer is more than 5μm, CS50 is less than 130+(20t-13)×15MPa, and the strengthening depth Doc of compressive stress layer is more than 0.18t.
[0074] Based on the above description that the chemically strengthened microcrystalline glass in this embodiment of the present application has a specific depth of compressive stress layer, a specific compressive stress intensity, and the relationship between the depth of the compressive stress layer and the compressive stress intensity, compared with the existing primary strengthened aluminosilicate glass and secondary strengthened lithium aluminosilicate glass, the chemically strengthened microcrystalline glass in this embodiment of the present application has a relatively high compressive stress and a much higher stress intensity than the existing aluminosilicate glass and microcrystalline glass, and therefore can resist crack growth. Compared with the general strengthened glass in the current life scenario (for example, the depth of the perforation caused by rough ground, which leads to the general failure of the current mobile phone in the life scenario, is usually 40-70 μm), the chemically strengthened microcrystalline glass in this embodiment of the present application is greatly improved in terms of perforation resistance against rough ground, and the height of the drop test using rough ground is higher than that of the existing aluminosilicate glass and microcrystalline glass. In FIG. 2, the curve of the primary strengthened aluminosilicate glass (with K / Na exchange) is obtained through a test performed by a common surface stress test device in the industry FSM-6000LEUV, the curve of the secondary strengthened lithium aluminosilicate glass (with both K / Na and Na / Li exchange) is obtained by synthesis through fitting tests performed by a surface stress test device in the industry FSM-6000LEUV and a Scattered Light Photoelastic Stress Meter SLP2000, and the curve of the chemically strengthened microcrystalline glass in this application is obtained through a test performed by using the SLP2000.
[0075] Further measurements have shown that the chemically strengthened microcrystalline glass in this embodiment of the present application further has the following relevant mechanical and optical properties:
[0076] In this embodiment, when the chemically strengthened microcrystalline glass is pressed and crushed by using a metal compression rod with a round head of 10 mm in diameter, the average size of the longest side of the fragments is 5 mm or more. Therefore, the chemically strengthened microcrystalline glass has suitable internal tensile stress and strong resistance to puncture on rough ground, thereby avoiding the risk of accidental explosion.
[0077] In this embodiment, when the thickness is 0.6 mm, the grit sandpaper drop test height of the chemically strengthened microcrystalline glass is 1.5 m or more. This reflects the excellent drop resistance of the chemically strengthened microcrystalline glass. The grit sandpaper drop test height data is obtained through testing in a scenario of 180# grit sandpaper / 200 g load. Specifically, the test target plane of the chemically strengthened microcrystalline glass in this application is placed facing down, and the other surface holds a standard 200 g load. The glass is first dropped from a height of 0.5 m, and the appearance of the glass is checked after each drop. If there is no problem, the height is increased by 0.1 m. The test is performed repeatedly until the glass breaks, and the height at which it breaks is recorded.
[0078] In this embodiment, when the chemically strengthened microcrystalline glass is stored in an environment of 85° C. and 85% humidity for 72 hours, no sodium salt precipitates on the outer surface of the chemically strengthened microcrystalline glass, which reflects the excellent thermal stability and moisture resistance of the chemically strengthened microcrystalline glass.
[0079] In this embodiment, when the thickness of the chemically strengthened microcrystalline glass is 0.8 mm or less, the average transmittance of light with a wavelength of 400 nm to 940 nm is 89.5% or more, the difference in single-point transmittance between the wavelength of 550 nm and the wavelength of 400 nm is less than 1%, the absolute value of the color coordinate b is 0.4 or less, and the haze is 0.15% or less, which reflects the excellent optical performance such as the light transmittance of the chemically strengthened microcrystalline glass.
[0080] Therefore, based on the depth of the compressive stress layer, the compressive stress intensity, and the relationship between the depth of the compressive stress layer and the compressive stress intensity, the chemically strengthened microcrystalline glass has high compressive stress intensity, excellent puncture resistance against rough ground, and high drop resistance, as described in the following Table 1. In addition, the chemically strengthened microcrystalline glass has excellent thermal stability, moisture resistance, and excellent optical performance such as light transmittance.
[0081] In this embodiment, the main crystalline phase of the raw microcrystalline glass used to form the chemically strengthened microcrystalline glass is either lithium metasilicate or β-quartz solid solution, the mass fraction of the total contained crystalline phase is 35%-75%, and the total content of the secondary crystalline phase is less than 5%. Through the control of the type of the main crystalline phase of the raw microcrystalline glass and the content of each crystalline phase, the Na / Li exchange layer contained in the chemically strengthened microcrystalline glass can be effectively prevented from being adversely affected by Li, and the CS50 range can be effectively controlled, thereby further improving the drilling resistance of the chemically strengthened microcrystalline glass to rough ground. In addition, the optical performance such as the light transmittance of the chemically strengthened microcrystalline glass can be further improved.
[0082] In some embodiments, the raw microcrystalline glass includes a main component and a nucleating agent. The main components include SiO2, Al2O3, B2O3, Li2O, Na2O, and K2O, and the content of SiO2+Al2O3+B2O3 is 58-85 mol%, and the content of Li2O+Na2O+K2O is 10-32 mol%. The nucleating agent includes TiO2, P2O5, and ZrO2, and the content of TiO2+P2O5+ZrO2 is 2-8 mol%. These components of the raw microcrystalline glass impart the above-mentioned types of main crystal phases and the content of each crystal phase to the raw microcrystalline glass and the chemically strengthened microcrystalline glass, thereby improving the drilling resistance of the chemically strengthened microcrystalline glass against rough ground and improving the optical performance such as light transmittance of the chemically strengthened microcrystalline glass.
[0083] In this embodiment, the glass matrix of the original microcrystalline glass can be prepared by using a melting and casting method or a calendaring method. In some embodiments, the glass matrix of the original microcrystalline glass is heat-treated in two stages: Heat treatment stage 1: Temperature is 500℃~600℃, treatment time is 0.1 hours~10 hours Heat treatment stage 2: The temperature is 640℃~800℃, and the treatment time is 0.1 hours~10 hours.
[0084] A two-step heat treatment is carried out on the glass matrix of the raw microcrystalline glass, so that the raw microcrystalline glass formed can obtain the required main crystalline phase and the content of the main crystalline phase, and adjust other secondary crystalline phases, thereby improving the drilling resistance and optical performance of the chemically strengthened microcrystalline glass against rough ground.
[0085] Due to the type of main crystalline phase and the content of each crystalline phase in the raw microcrystalline glass, tests have shown that the raw microcrystalline glass also has excellent mechanical properties, such as Young's modulus, and excellent optical properties, such as light transmittance.
[0086] For example, in this embodiment, when the thickness of the raw microcrystalline glass is 0.8 mm or less, and the average transmittance of light with a wavelength of 400 nm to 940 nm is 89.5% or more, the difference in single-point transmittance between the wavelength of 550 nm and the wavelength of 400 nm is less than 1%, the absolute value of the color coordinate b is 0.3 or less, and the haze is 0.14 or less. Through controlling the type of main crystal phase and the content of each crystal phase of the raw microcrystalline glass, the raw microcrystalline glass has excellent optical properties such as light transmittance and has stable optical properties.
[0087] In this embodiment, the Young's modulus of the original microcrystalline glass is 95 GPa or more. Based on the type of the main crystal phase of the original microcrystalline glass and the content of each crystal phase, the original microcrystalline glass is endowed with a high Young's modulus, and as a result, the chemically strengthened microcrystalline glass is endowed with a high Young's modulus, for example, the high Young's modulus of the chemically strengthened microcrystalline glass is 95 GPa or more. In this way, the chemically strengthened microcrystalline glass is endowed with a storage space capable of accommodating a larger compressive stress, and conditions are provided for increasing the compressive stress of the chemically strengthened microcrystalline glass. In addition, the original microcrystalline glass and the chemically strengthened microcrystalline glass are endowed with high impact resistance. For example, tests have shown that the chemically strengthened microcrystalline glass can withstand an impact of about 25-30 GPa, which is higher than that of existing aluminosilicate glass, thereby effectively lowering the requirement and dependency of the chemically strengthened microcrystalline glass on the K / Na exchange layer.
[0088] In this embodiment, the surface layer of the chemically strengthened microcrystalline glass further has a K / Na exchange layer. The K / Na exchange layer is further formed on the surface layer of the chemically strengthened microcrystalline glass, that is, a potassium layer is added to the surface layer of the chemically strengthened microcrystalline glass. Based on the high puncture resistance of the chemically strengthened microcrystalline glass against rough ground, the drop resistance of the chemically strengthened microcrystalline glass against rough ground is further improved, and the impact resistance of the chemically strengthened microcrystalline glass is further improved.
[0089] In addition, based on the fact that the chemically strengthened microcrystalline glass in this embodiment of the present application has a high Young's modulus, for example, a Young's modulus of 95 GPa or more, a high Young's modulus supports relatively good impact resistance, thereby effectively reducing the dependency on the K / Na exchange layer. According to the comparison of the stress curve shown in FIG. 2 with the curve of the existing primary strengthened aluminosilicate glass, the chemically strengthened microcrystalline glass in this embodiment of the present application does not require a relatively large K / Na exchange layer. For example, in this embodiment, the thickness of the K / Na exchange layer included in the chemically strengthened microcrystalline glass in the above embodiment is 3 μm or less. Through the control of the thickness of the K / Na exchange layer (potassium layer), the impact resistance and drop resistance of the chemically strengthened microcrystalline glass against rough ground can be further improved. Based on the depth of the compressive stress layer, the compressive stress intensity, and the relationship between the depth of the compressive stress layer and the compressive stress intensity, the requirement for the thickness of the K / Na exchange layer can be effectively reduced.
[0090] Based on the fact that the chemically strengthened microcrystalline glass in the above embodiment has excellent optical performance such as excellent perforation resistance, drop resistance, and light transmittance against rough ground, the chemically strengthened microcrystalline glass may further have a high Young's modulus and high impact resistance. The chemically strengthened microcrystalline glass in the present embodiment of the present application may be any one of chemically strengthened microcrystalline glass having a two-dimensional structure, chemically strengthened microcrystalline glass having a 2.5-dimensional structure, or chemically strengthened microcrystalline glass having a three-dimensional structure. The chemically strengthened microcrystalline glass has excellent perforation resistance and optical performance against the above rough ground. This expands the application scope of the chemically strengthened microcrystalline glass and improves the quality and performance stability of the corresponding products.
[0091] When the chemically strengthened microcrystalline glass in the above embodiment is a chemically strengthened microcrystalline glass having a two-dimensional structure or a chemically strengthened microcrystalline glass having a 2.5-dimensional structure, the CS50 and Doc of the chemically strengthened microcrystalline glass in this embodiment satisfy the following: That is, CS50 / (Doc-50) is 1.4 to 6.
[0092] In some other embodiments, when the thickness of the chemically strengthened microcrystalline glass is 0.8 mm or less, the average transmittance of light with a wavelength of 400 nm to 940 nm is 89.5% or more, the difference in single-point transmittance between a wavelength of 550 nm and a wavelength of 400 nm is less than 1%, the absolute value of the color coordinate b is 0.3 or less, and the haze is 0.14% or less.
[0093] Therefore, when the chemically strengthened microcrystalline glass in the above embodiment is a chemically strengthened microcrystalline glass having a two-dimensional structure or a chemically strengthened microcrystalline glass having a 2.5-dimensional structure, the chemically strengthened microcrystalline glass has excellent drilling resistance and light transmittance against rough ground.In addition, compared with the optical performance of the original microcrystalline glass, the optical performance such as light transmittance of the chemically strengthened microcrystalline glass is stable.
[0094] When the chemically strengthened microcrystalline glass in the above embodiment is a chemically strengthened microcrystalline glass having a three-dimensional structure, in this embodiment, the long side bending angle of the chemically strengthened microcrystalline glass having a three-dimensional structure is 15° to 89°. In addition, the CS50, Doc, and the relationship between CS50 and Doc of the chemically strengthened microcrystalline glass satisfy the characteristics shown in the above formulas 1-1 to 1-3. The chemically strengthened microcrystalline glass still has excellent perforation resistance to rough ground, and still has excellent impact resistance naturally. The measured optical properties of the chemically strengthened microcrystalline glass have been described above. The average transmittance of light with a wavelength of 400 nm to 940 nm is 89.5% or more, the difference in single-point transmittance between the wavelength of 550 nm and the wavelength of 400 nm is less than 1%, the absolute value of the color coordinate b is 0.4 or less, and the haze is 0.15% or less. There is a slight difference compared to the optical performance of the original microcrystalline glass, but the difference is not obvious. Therefore, when the chemically strengthened microcrystalline glass in the above embodiment is a chemically strengthened microcrystalline glass having a three-dimensional structure, the chemically strengthened microcrystalline glass still has excellent optical performance such as light transmittance.
[0095] According to another aspect, the present embodiment provides a method for preparing the above-mentioned chemically strengthened microcrystalline glass in the present embodiment. As shown in Figure 3, the process procedure of the method for preparing the chemically strengthened microcrystalline glass in the present embodiment of the present application includes the following steps:
[0096] S01: In a sodium salt-containing bath, a primary chemical strengthening treatment is carried out on raw microcrystalline glass to be subjected to chemical strengthening treatment, thereby forming a Na / Li exchange layer.
[0097] In the primary chemical strengthening process, sodium ions in the sodium-containing salt bath will diffuse to the surface layer of the raw microcrystalline glass by thermodynamic behavior and exchange with lithium ions in the surface layer of the raw microcrystalline glass, i.e., sodium-lithium ion exchange is carried out, so that a Na / Li exchange layer is formed on the surface layer of the raw microcrystalline glass. In addition, through the control of the primary chemical strengthening process, the chemically strengthened microcrystalline glass formed by chemical strengthening can have the depth of the compressive stress layer, the compressive stress intensity CS50 range, and the relationship between the depth of the compressive stress layer and the compressive stress intensity CS50 range (shown in the above formulas 1-1 to 1-3) of the chemically strengthened microcrystalline glass in the above embodiment of the present application. In this way, the prepared chemically strengthened microcrystalline glass is endowed with a relatively high compressive stress and a greatly improved stress intensity, can resist crack growth, and has excellent perforation resistance against rough ground. In addition, in the present application, the chemical strengthening conditions for the preparation method of the chemically strengthened microcrystalline glass in the present application are easy to control, so that the prepared chemically strengthened microcrystalline glass has stable performance, high efficiency, and reduced preparation cost.
[0098] In this embodiment, the sodium-containing salt bath contains NaNO3 or a salt mixture of NaNO3 and KNO3. When the sodium-containing salt bath is a salt mixture containing NaNO3 and KNO3, the content of NaNO3 is 50wt% or more in the salt mixture of NaNO3 and KNO3. In this embodiment, for the primary chemical strengthening treatment, the temperature is 380℃-450℃, and the strengthening time is 0.5 hours-6 hours. Through the control of the type of sodium-containing salt bath, the content of NaNO3, and the primary chemical strengthening treatment, the effect of the chemical strengthening treatment on the raw microcrystalline glass is improved, and the depth of the compressive stress layer and the compressive stress intensity CS50 range of the formed chemically strengthened microcrystalline glass are optimized, so that the compressive stress of the chemically strengthened microcrystalline glass is increased, and the drilling resistance and light transmittance performance of the chemically strengthened microcrystalline glass against rough ground are improved.
[0099] In addition, the raw microcrystalline glass to be subjected to the chemical strengthening treatment is the raw microcrystalline glass of the above-mentioned chemically strengthened microcrystalline glass, for example, the main crystal phase is either lithium metasilicate or β-quartz solid solution, the mass fraction of the total crystal phase content is 35% to 75%, and the total content of the secondary crystal phase is less than 5%. In a specific embodiment, the raw microcrystalline glass includes a main component and a nucleating agent. The main components include SiO2, Al2O3, B2O3, Li2O, Na2O, and K2O, and the content of SiO2+Al2O3+B2O3 is 58 to 85 mol%, and the content of Li2O+Na2O+K2O is 10 to 32 mol%. The nucleating agent includes TiO2, P2O5, and ZrO2, and the content of TiO2+P2O5+ZrO2 is 2 to 8 mol%.
[0100] In this embodiment, when the prepared chemically strengthened microcrystalline glass is a chemically strengthened microcrystalline glass having a three-dimensional structure, before carrying out a primary chemical strengthening treatment on the raw microcrystalline glass to be chemically strengthened in a sodium salt-containing bath, the method further includes carrying out the following hot bending treatment on the raw microcrystalline glass: carrying out a hot bending treatment on the raw microcrystalline glass at 650°C to 750°C to form a three-dimensional raw microcrystalline glass, the time of each hot bending treatment is 30 seconds to 120 seconds, and the pressure of the hot bending treatment is 0.1 MPa to 0.9 MPa.
[0101] The three-dimensional raw microcrystalline glass is formed by carrying out a hot bending process on the raw microcrystalline glass, so that after a primary chemical strengthening process or a further secondary chemical strengthening process, a chemically strengthened microcrystalline glass having a three-dimensional structure can be formed, ensuring that the chemically strengthened microcrystalline glass having a three-dimensional structure has high compressive stress, excellent puncture resistance against rough ground, and excellent light transmittance performance.
[0102] In certain embodiments, the long side bending angle of the three-dimensional original microcrystalline glass is 15° to 89°. In some other specific embodiments, the absolute value of the difference in the value change of the color coordinate b of the three-dimensional original microcrystalline glass is 0.1 or less. Through controlling the conditions of the above hot bending process, the prepared three-dimensional original microcrystalline glass has the required long side bending angle and has stable optical performance.
[0103] Compared with existing microcrystalline glasses such as those mentioned in the background art and whose main crystal phases are petalite and lithium disilicate, the hot bending temperature of existing microcrystalline glasses whose main crystal phases are petalite and lithium disilicate is greater than 750°C, and the size of the crystal phase grows in the hot bending process, resulting in a rapid deterioration of the optical performance after three-dimensional forming (the absolute value of chromatic aberration b is 2 or more, and the haze is 0.25% or more). The requirements for the application of hot bending three-dimensional CG covers cannot be met. In contrast, the above-mentioned original microcrystalline glasses whose main crystal phases are either lithium metasilicate and β-quartz solid solution in this embodiment of the present application use the maximum hot bending temperature in the range of 650°C to 750°C described above. Before and after hot bending, the absolute value of the difference in the value change of the color coordinate b of the glass is 0.1 or less, the absolute value of the color coordinate b is 0.4 or less, and the haze is 0.14% or less. The requirements for the application of three-dimensional hot bending three-dimensional CG covers can be met.
[0104] In this embodiment, after the primary chemical strengthening treatment, the method further includes step S02 shown in FIG. 3, i.e., performing a secondary chemical strengthening treatment on the chemically strengthened microcrystalline glass having a Na / Li exchange layer formed in a potassium salt-containing bath to form a K / Na exchange layer.
[0105] In the secondary chemical strengthening treatment process, the potassium ions in the potassium-containing salt bath diffuse into the surface layer of the chemically strengthened microcrystalline glass according to thermodynamic behavior and exchange with the sodium ions in the Na / Li exchange layer, i.e., potassium-sodium ion exchange is carried out and a K / Na exchange layer is formed on the surface layer of the chemically strengthened microcrystalline glass, thereby further improving the impact resistance and drop resistance on rough ground of the chemically strengthened microcrystalline glass.
[0106] In this embodiment, the potassium-containing salt bath contains KNO3 or a salt mixture of NaNO3 and KNO3. When the potassium-containing salt bath is a salt mixture containing NaNO3 and KNO3, the content of KNO3 is 80%wt or more in the salt mixture of NaNO3 and KNO3. In this embodiment, in the secondary chemical strengthening treatment, the temperature is 380℃-450℃, and the strengthening time is 0.2 hours-1 hour. Through the control of the type of potassium-containing salt bath, the content of KNO3, and the secondary chemical strengthening treatment, the effect of the secondary chemical strengthening treatment is improved, and the impact resistance and drop resistance on rough ground of the chemically strengthened microcrystalline glass are further improved.
[0107] In addition, the chemically strengthened microcrystalline glass in the above-mentioned embodiment of the present application and the chemically strengthened microcrystalline glass prepared by using the preparation method thereof are compared with existing microcrystalline glasses, such as the microcrystalline glass whose main crystal phase is petalite and lithium disilicate, mentioned in the background art. The existing microcrystalline glass whose main crystal phase is petalite and lithium disilicate has a relatively high crystallinity (this material contains multiple main crystal phases and requires a relatively high crystallinity to maintain good optical performance), and therefore requires a higher chemical strengthening temperature / longer chemical strengthening time, since a higher potential energy is required for ion exchange. In addition, the microcrystalline glass is affected by the concentration of Li in the chemical strengthening boiler water, and is limited by the inhibition by Li in Na / Li exchange in the chemical strengthening process, requiring precise control over the concentration of Li in the chemical strengthening process. Therefore, for the chemically strengthened microcrystalline glass formed by chemically strengthening the existing microcrystalline glass, the CS50 is less than 130+(20t-13)×15MPa. However, the chemically strengthened microcrystalline glass in this embodiment of the present application, especially the chemically strengthened microcrystalline glass whose main crystal phase includes either lithium metasilicate or β-quartz solid solution, has a relatively low crystallinity, for example, a crystallinity of 75wt% or less. The chemical strengthening process is not affected by Li. The CS50, Doc, and the relationship between CS50 and Doc of the chemically strengthened microcrystalline glass obtained by the chemical strengthening process satisfy the characteristics shown in the above formulas 1-1 to 1-3. In particular, CS50 is 130+(20t-13)×15MPa to 230+(20t-13)×15MPa. In this way, better drilling resistance against rough ground is obtained.
[0108] According to yet another aspect, based on the above-mentioned chemically strengthened microcrystalline glass and its preparation method, the embodiment of the present application provides an electronic device. The electronic device in this embodiment of the present application includes a glass component, and the glass component is the chemically strengthened microcrystalline glass in the above-mentioned embodiment of the present application. In this way, the chemically strengthened microcrystalline glass in this embodiment of the present application has excellent perforation resistance, optical performance, and impact resistance against the above-mentioned rough ground, so that the glass component is endowed with excellent drop resistance and crash resistance, and high strength. Therefore, the electronic device in this embodiment of the present application including the glass component also has excellent drop resistance and crash resistance and impact resistance, and the electronic device has high quality and high operation performance stability.
[0109] In this embodiment, the glass component of the electronic device includes at least one of a display cover, a protective cover, or a protective screen. The glass component has excellent light transmission and excellent display effect, and can further provide excellent protection. In addition, the glass component has drop resistance and impact resistance and high strength, so that the electronic device is stable. The glass component can further be any one of chemically strengthened microcrystalline glass with a two-dimensional structure, chemically strengthened microcrystalline glass with a 2.5-dimensional structure, or chemically strengthened microcrystalline glass with a three-dimensional structure. This extends the application scope of the chemically strengthened microcrystalline glass and improves the quality and performance stability of the corresponding electronic device.
[0110] In this embodiment, the electronic device includes at least one of a communication mobile terminal, an electronic watch, a band, and a computer. In a specific embodiment, when the electronic device is a communication mobile terminal such as a mobile phone, the glass component included in the electronic device can be used as the front cover or back cover of the mobile phone. Because the electronic device includes the glass component, the electronic device has good drop resistance, or even has good impact resistance and has high strength, so that the performance of the electronic device is stable.
[0111] The above chemically strengthened microcrystalline glass and its preparation method are described in detail below with reference to certain embodiments. [Embodiment 1]
[0112] This embodiment provides a chemically strengthened microcrystalline glass based on β-quartz solid solution with three-dimensional structure and a chemical strengthening method thereof. The relevant performance of the chemically strengthened microcrystalline glass and the relevant process parameters of the chemical strengthening method thereof are separately described in Table 2 below.
[0113] The method for preparing chemically strengthened microcrystalline glass comprises the following steps.
[0114] S1: Raw microcrystalline glass and its preparation
[0115] (1) The glass matrix is prepared by using melting and casting method. The composition of the glass matrix is SiO2+Al2O3+B2O3=85mol%, Li2O+Na2O+K2O=10mol%. For the nucleating agent, TiO2+P2O5+ZrO2=2mol%, and another component is MgO.
[0116] (2) A two-step heat treatment is carried out on the prepared glass substrate to obtain the required crystal phase. In the first heat treatment step, the temperature is 600°C and the treatment time is 0.1 hours. In the second heat treatment step, the temperature is 750°C-900°C and the treatment time is 0.1 hours. The main crystal phase of the obtained crystal is β-quartz solid solution, and the crystallinity obtained through XRD test is 35wt%.
[0117] S2: Three-dimensional raw microcrystalline glass and its preparation.
[0118] The β-quartz solid solution based microcrystalline glass prepared in step S1 is cut / ground / polished into a raw glass sheet with a thickness of 0.35 mm. Then, hot bending is carried out by using a three-dimensional graphite mold to form a three-dimensional model, the maximum hot bending temperature is 650°C, the hot bending compressive stress is 0.9 MPa, and the single-process hot bending time is 30 seconds.
[0119] S3: The three-dimensional glass obtained after hot bending in step S2 is polished on the concave and convex sides by using a three-dimensional polishing brush (the thickness after polishing is 0.3 mm), and then a chemical strengthening treatment is carried out to form a β-quartz solid solution-based chemically strengthened microcrystalline glass with a three-dimensional structure, and the strengthening conditions for chemical strengthening are described in Table 2. [Embodiment 2]
[0120] This embodiment provides a lithium metasilicate-based chemically strengthened microcrystalline glass with 2.5-dimensional structure and its chemical strengthening method.The relevant performance of the chemically strengthened microcrystalline glass and the relevant process parameters of its chemical strengthening method are separately described in Table 2 below.
[0121] The method for preparing chemically strengthened microcrystalline glass comprises the following steps.
[0122] S1: Raw microcrystalline glass and its preparation.
[0123] (1) The glass matrix is prepared by using melting and casting method. The composition of the glass matrix is SiO2+Al2O3+B2O3=58mol%, Li2O+Na2O+K2O=32mol%. As for the nucleating agent, TiO2+P2O5+ZrO2=8mol%, and another component is 2mol% MgO.
[0124] (2) A two-stage heat treatment is carried out on the prepared glass substrate to obtain the required crystalline phase. In the first heat treatment stage, the temperature is 500°C and the treatment time is 10 hours. In the second heat treatment stage, the temperature is 640°C and the treatment time is 10 hours. The main crystalline phase of the obtained crystal is lithium metasilicate, and the crystallinity obtained through XRD test is 75wt%.
[0125] S2: 2.5-dimensional original microcrystalline glass and its preparation.
[0126] The lithium metasilicate based raw microcrystalline glass prepared in step S1 is cut, ground, processed by using a computer numerical control (CNC) machine, and polished into a 0.65 mm carrier with a 2.5-dimensional structure.
[0127] S3: The 2.5-dimensional raw microcrystalline glass in step S2 is polished on the concave and convex sides by using an abrasive brush, and then a chemical strengthening process is carried out to form a lithium metasilicate-based chemically strengthened microcrystalline glass with a 2.5-dimensional structure, where the thickness of the final product is 0.6 mm, and the strengthening conditions of the chemical strengthening are described in Table 2. [Embodiment 3]
[0128] This embodiment provides a lithium metasilicate-based chemically strengthened microcrystalline glass with three-dimensional structure and its chemical strengthening method.The relevant performance of the chemically strengthened microcrystalline glass and the relevant process parameters of its chemical strengthening method are separately described in Table 2 below.
[0129] The method for preparing chemically strengthened microcrystalline glass comprises the following steps.
[0130] S1: Raw microcrystalline glass and its preparation.
[0131] (1) The glass matrix is prepared by using melting and casting method. The composition of the glass matrix is SiO2+Al2O3+B2O3=65mol%, Li2O+Na2O+K2O=30mol%. The nucleating agent is TiO2+P2O5+ZrO2=5mol%.
[0132] (2) A two-stage heat treatment is carried out on the prepared glass substrate to obtain the required crystalline phase. In the first heat treatment stage, the temperature is 550°C and the treatment time is 6 hours. In the second heat treatment stage, the temperature is 800°C and the treatment time is 2 hours. The main crystalline phase of the obtained crystal is lithium metasilicate, and the crystallinity obtained through XRD test is 65wt%.
[0133] S2: Three-dimensional raw microcrystalline glass and its preparation.
[0134] The lithium metasilicate-based raw microcrystalline glass prepared in step S1 is cut / ground / polished into a raw glass sheet with a thickness of 0.7 mm. Then, hot bending is carried out by using a three-dimensional graphite mold to form a three-dimensional model, the maximum hot bending temperature is 750°C, the hot bending compressive stress is 0.1 MPa, and the single-process hot bending time is 120 seconds.
[0135] S3: The raw microcrystalline glass in step S2 is polished on the concave and convex sides by using a three-dimensional polishing brush, and then a chemical strengthening process is carried out to form a lithium metasilicate-based chemically strengthened microcrystalline glass with a three-dimensional structure, where the thickness of the final product is 0.65 mm, and the strengthening conditions of the chemical strengthening are described in Table 2. [Embodiment 4]
[0136] This embodiment provides a lithium metasilicate-based chemically strengthened microcrystalline glass with 2.5-dimensional structure and its chemical strengthening method.The relevant performance of the chemically strengthened microcrystalline glass and the relevant process parameters of its chemical strengthening method are separately described in Table 2 below.
[0137] The method for preparing chemically strengthened microcrystalline glass comprises the following steps.
[0138] S1: Raw microcrystalline glass and its preparation.
[0139] (1) The glass matrix is prepared by using melting and casting method. The composition of the glass matrix is SiO2+Al2O3+B2O3=65mol%, Li2O+Na2O+K2O=30mol%. The nucleating agent is TiO2+P2O5+ZrO2=5mol%.
[0140] (2) A two-stage heat treatment is carried out on the prepared glass substrate to obtain the required crystalline phase. In the first heat treatment stage, the temperature is 550°C and the treatment time is 6 hours. In the second heat treatment stage, the temperature is 800°C and the treatment time is 2 hours. The main crystalline phase of the obtained crystal is lithium metasilicate, and the crystallinity obtained through XRD test is 65wt%.
[0141] S2: 2.5-dimensional original microcrystalline glass and its preparation.
[0142] The lithium metasilicate based raw microcrystalline glass prepared in step S1 is cut / ground / polished into 1 mm thick green glass sheets with a 2.5 dimensional structure.
[0143] S3: In step S2, a chemical strengthening process is carried out on the 2.5D raw microcrystalline glass, and the strengthening conditions of the chemical strengthening are described in Table 1.
[0144] Related performance tests for chemically strengthened microcrystalline glass:
[0145] The related performance tests described in the following Table 2 are carried out separately according to the above-mentioned Embodiments 1 to 4. The test method is as follows. The test results are described in the following Table 1. Table 1 [Table 1]
[0146] It can be seen from Table 1 that in each embodiment, the depth Doc of the compressive stress layer of the chemically strengthened microcrystalline glass and the thickness of the chemically strengthened microcrystalline glass satisfy that Doc is 0.15t to 0.22t. The compressive stress intensity CS50 at a strengthening depth of 50 μm in the surface layer of each type of chemically strengthened microcrystalline glass and the thickness of the chemically strengthened microcrystalline glass satisfy that CS50 is 130 + (20t-13) × 15 MPa to 230 + (20t^13) × 15 MPa. CS50 and Doc satisfy the relationship that CS50 / (Doc-50) is 1 to 7.5. In addition, the chemically strengthened microcrystalline glass has high perforation resistance against rough ground, excellent optical performance such as light transmittance, and excellent thermal stability and moisture resistance.
[0147] Furthermore, the existing 0.6mm thick primary strengthened aluminosilicate glass (with K / Na exchange) and 0.6mm thick secondary strengthened lithium aluminosilicate glass (with both K / Na and Na / Li exchange) in the industry are compared with the original microcrystalline glass and the chemical strengthened microcrystalline glass obtained by using the same chemical strengthening process as in embodiment 3, and are therefore used as examples to carry out CS50 (MPa) test and drop height test using 180# grit sandpaper on these three types of glass. The primary strengthened aluminosilicate glass, secondary strengthened lithium aluminosilicate glass and chemical strengthened microcrystalline glass in this embodiment of the present application have the same structure and the same thickness. The test results are described in Table 2. Table 2 [Table 2]
[0148] It can be seen from Table 2 that the CS50 and grit sandpaper drop test heights for the chemically strengthened microcrystalline glass in this embodiment of the present application are significantly higher than the CS50 and grit sandpaper drop test heights for the existing primary strengthened aluminosilicate glass and secondary strengthened lithium aluminosilicate glass. Therefore, the puncture resistance of the chemically strengthened microcrystalline glass in this embodiment of the present application against rough ground is significantly improved. Therefore, the chemically strengthened microcrystalline glass provided in this embodiment of the present application is used in electronic products. For example, the glass is used as a front cover or back cover of a mobile phone, specifically, it can be a 2D cover, 2.5D cover, 3D cover, or the like, thereby improving the drop resistance of mobile phones and other electronic products and giving the corresponding electronic products excellent impact resistance. The glass can further improve the impact resistance of mobile phones and other electronic products, making the performance of the electronic products stable.
[0149] The above description is merely an exemplary embodiment of the present application, and is not used to limit the present application. Any modification, equivalent replacement, or improvement made in the spirit and principle of the present application shall belong to the protection scope of the present application. According to this specification, the configurations described in the following items are also disclosed. (Item 1) A chemically strengthened microcrystalline glass having a Na / Li exchange layer, the depth Doc of the compressive stress layer of the chemically strengthened microcrystalline glass being 0.15t to 0.22t; A chemically strengthened microcrystalline glass, wherein the compressive stress strength CS50 at a strengthening depth of 50 μm in the surface layer of the chemically strengthened microcrystalline glass is 130+(20t-13)×15MPa to 230+(20t-13)×15MPa, CS50 and Doc satisfy CS50 / (Doc-50) of 1.4 to 6 (unit: MPa / μm), and t is the overall thickness of the chemically strengthened microcrystalline glass. (Item 2) When the chemically strengthened microcrystalline glass is pressed and crushed by a metal compression rod having a round head with a diameter of 10 mm, the average size of the longest side of the fragments is 5 mm or more; and / or and / or, when the thickness of the chemically strengthened microcrystalline glass is 0.6 mm, the height of a grit sandpaper drop test for the chemically strengthened microcrystalline glass is 1.5 m or more; and / or When the chemically strengthened microcrystalline glass is stored in an environment at a temperature of 85° C. and a humidity of 85% for 72 hours, sodium salts do not precipitate on the outer surface of the chemically strengthened microcrystalline glass, and / or When the thickness of the chemically strengthened microcrystalline glass is 0.8 mm or less, the average transmittance of light with a wavelength of 400 nm to 940 nm is 89.5% or more, the difference in single-point transmittance between the wavelength of 550 nm and the wavelength of 400 nm is less than 1%, the absolute value of the color coordinate b is 0.4 or less, and the haze is 0.15% or less; Item 1. The chemically strengthened microcrystalline glass according to item 1. (Item 3) 3. The chemically strengthened microcrystalline glass according to item 1 or 2, wherein the main crystalline phase of the raw microcrystalline glass used to form the chemically strengthened microcrystalline glass is either lithium metasilicate or a β-quartz solid solution, the mass fraction of the total crystalline phase content is 35% to 75%, and the total content of secondary crystalline phases is less than 5%. (Item 4) 4. The chemically strengthened microcrystalline glass according to item 3, wherein the raw microcrystalline glass comprises a main component and a nucleating agent, the main components comprising SiO2, Al2O3, B2O3, Li2O, Na2O, and K2O, the content of SiO2+Al2O3+B2O3 being 58-85 mol% and the content of Li2O+Na2O+K2O being 10-32 mol%, and the nucleating agent comprises TiO2, P2O5, and ZrO2, the content of TiO2+P2O5+ZrO2 being 2-8 mol%. (Item 5) The glass matrix of the original microcrystalline glass is prepared by using a melt-casting method or a calendaring method; and / or The glass matrix of the raw microcrystalline glass is prepared in two steps: Heat treatment stage 1: the temperature is 500°C to 600°C, the treatment time is 0.1 hours to 10 hours, and Heat treatment stage 2: Temperature is 640℃~800℃, treatment time is 0.1 hours~10 hours 4. The chemically strengthened microcrystalline glass according to claim 3, which is heat treated by (Item 6) 4. The chemically strengthened microcrystalline glass according to item 3, wherein the Young's modulus of the chemically strengthened microcrystalline glass is 95 GPa or more. (Item 7) 4. The chemically strengthened microcrystalline glass according to item 3, wherein the surface layer of the chemically strengthened microcrystalline glass further comprises a K / Na exchange layer. (Item 8) 8. The chemically strengthened microcrystalline glass according to item 7, wherein the K / Na exchange layer has a thickness of 3 μm or less. (Item 9) Item 2. The chemically strengthened microcrystalline glass according to item 1, wherein the chemically strengthened microcrystalline glass is any one of a chemically strengthened microcrystalline glass having a two-dimensional structure, a chemically strengthened microcrystalline glass having a 2.5-dimensional structure, and a chemically strengthened microcrystalline glass having a three-dimensional structure. (Item 10) The chemically strengthened microcrystalline glass according to item 9, wherein the chemically strengthened microcrystalline glass has a two-dimensional structure and / or a 2.5-dimensional structure, and the absolute value of the color coordinate b is 0.3 or less and the haze is 0.14% or less for the chemically strengthened microcrystalline glass having a two-dimensional structure and / or the chemically strengthened microcrystalline glass having a 2.5-dimensional structure. (Item 11) The chemically strengthened microcrystalline glass has a three-dimensional structure, and the long side bending angle of the chemically strengthened microcrystalline glass having a three-dimensional structure is 15 ° to 89 °, and / or For the chemically strengthened microcrystalline glass having a three-dimensional structure, the absolute value of the color coordinate b is 0.4 or less, and the haze is 0.15% or less; Item 10. The chemically strengthened microcrystalline glass according to item 9. (Item 12) 1. A method for preparing chemically strengthened microcrystalline glass, comprising: A preparation method comprising the step of performing a primary chemical strengthening treatment on a raw microcrystalline glass to be subjected to the chemical strengthening treatment in a sodium salt-containing bath to form a Na / Li exchange layer. (Item 13) The sodium salt-containing bath contains NaNO3 or a salt mixture of NaNO3 and KNO3, in which the NaNO3 content is 50 wt% or more, and / or Item 13. The method according to item 12, wherein in the first chemical strengthening treatment, the temperature is 380°C to 450°C, and the strengthening time is 0.5 hours to 6 hours. (Item 14) Item 14. The method according to item 12 or 13, further comprising the step of: performing a secondary chemical strengthening treatment on the chemically strengthened microcrystalline glass having the Na / Li exchange layer formed thereon in a potassium salt-containing bath to form a K / Na exchange layer after the primary chemical strengthening treatment. (Item 15) The potassium salt-containing bath contains KNO3 or a salt mixture of NaNO3 and KNO3, in which the content of KNO3 in the salt mixture of NaNO3 and KNO3 is 80 wt% or more; and / or Item 15. The method according to item 14, wherein in the secondary chemical strengthening treatment, the temperature is 380°C to 450°C, and the strengthening time is 0.2 hours to 1 hour. (Item 16) In a sodium salt-containing bath, before carrying out a primary chemical strengthening treatment on the raw microcrystalline glass to be subjected to the chemical strengthening treatment, the raw microcrystalline glass is A step of forming a three-dimensional raw microcrystalline glass by performing a hot bending process on the raw microcrystalline glass at 650°C to 750°C, the time of each hot bending process being 30 seconds to 120 seconds, and the pressure of the hot bending process being 0.1 MPa to 0.9 MPa. Item 13. The preparation method according to item 12, further comprising the step of: (Item 17) 13. An electronic device comprising a glass component, the glass component being the chemically strengthened microcrystalline glass described in item 1 or the chemically strengthened microcrystalline glass prepared using the preparation method described in item 12.
Claims
1. A chemically strengthened microcrystalline glass having a K / Na exchange layer, the depth Doc of the compressive stress layer of the chemically strengthened microcrystalline glass being 0.15t to 0.22t; The compressive stress strength CS50 at a strengthening depth of 50 μm in the surface layer of the chemically strengthened microcrystalline glass is 130 + (20t - 13) × 15 MPa to 230 + (20t - 13) × 15 MPa; CS50 and Doc satisfy the requirement that CS50 / (Doc-50) is 1.4 to 6 (in MPa / μm), t is the overall thickness (mm) of the chemically strengthened microcrystalline glass, the value of t is 0.3 to 0.8, and the thickness of the K / Na exchange layer is 3 μm or less; Chemically strengthened microcrystalline glass.
2. 2. The chemically strengthened microcrystalline glass of claim 1, wherein the predominant crystalline phase of the chemically strengthened microcrystalline glass is either lithium metasilicate or β-quartz solid solution.
3. The chemically strengthened microcrystalline glass of claim 1 further comprising a Na / Li exchanged layer.
4. The chemically strengthened microcrystalline glass according to claim 3, wherein the mass fraction of the total crystalline phase contained in the chemically strengthened microcrystalline glass is 35% to 75%.
5. 5. The chemically strengthened microcrystalline glass of claim 4, wherein the total content of secondary crystalline phases in the chemically strengthened microcrystalline glass is less than 5%.
6. 2. The chemically strengthened microcrystalline glass of claim 1, wherein when the chemically strengthened microcrystalline glass is pressed and crushed by a metal compression rod having a round head with a diameter of 10 mm, the average size of the longest side of the fragments is 5 mm or more.
7. 2. The chemically strengthened microcrystalline glass according to claim 1, wherein the chemically strengthened microcrystalline glass has a grit sandpaper drop test height of 1.5 m or more when the chemically strengthened microcrystalline glass has a thickness of 0.6 mm.
8. 2. The chemically strengthened microcrystalline glass of claim 1, wherein sodium salts do not precipitate on the outer surface of the chemically strengthened microcrystalline glass when the chemically strengthened microcrystalline glass is stored in an environment at a temperature of 85° C. and a humidity of 85% for 72 hours.
9. 2. The chemically strengthened microcrystalline glass according to claim 1, wherein when the thickness of the chemically strengthened microcrystalline glass is 0.8 mm or less, the average transmittance of light with a wavelength of 400 nm to 940 nm is 89.5% or more, the difference in single-point transmittance between a wavelength of 550 nm and a wavelength of 400 nm is less than 1%, the absolute value of the color coordinate b is 0.4 or less, and the haze is 0.15% or less.
10. The chemically strengthened microcrystalline glass according to claim 1 , wherein the Young's modulus of the chemically strengthened microcrystalline glass is 95 GPa or more.
11. The chemically strengthened microcrystalline glass according to claim 1, wherein the chemically strengthened microcrystalline glass is any one of a chemically strengthened microcrystalline glass having a two-dimensional structure, a chemically strengthened microcrystalline glass having a 2.5-dimensional structure, and a chemically strengthened microcrystalline glass having a three-dimensional structure.
12. The chemically strengthened microcrystalline glass is the chemically strengthened microcrystalline glass having a two-dimensional structure and / or the chemically strengthened microcrystalline glass having a 2.5-dimensional structure, and for the chemically strengthened microcrystalline glass having a two-dimensional structure and / or the chemically strengthened microcrystalline glass having a 2.5-dimensional structure, the absolute value of the color coordinate b is 0.3 or less, and the haze is 0.14% or less. The chemically strengthened microcrystalline glass according to claim 11.
13. The chemically strengthened microcrystalline glass is a three-dimensional structure, and the long side bending angle of the chemically strengthened microcrystalline glass having a three-dimensional structure is 15° to 89°, and / or For the chemically strengthened microcrystalline glass having a three-dimensional structure, the absolute value of the color coordinate b is 0.4 or less, and the haze is 0.15% or less; The chemically strengthened microcrystalline glass of claim 11.
14. Further containing the main ingredients, The main component is SiO 2 , Al 2 O 3 , B 2 O 3 , Li 2 O, Na 2 O and K 2 Contains O and SiO 2 +Al 2 O 3 +B 2 O 3 The content of Li is 58 to 85 mol%, 2 O+Na 2 O+K 2 The chemically strengthened microcrystalline glass according to any one of claims 1 to 13, wherein the O content is 10 to 32 mol%.
15. Further comprising a nucleating agent; The nucleating agent is TiO 2 , P 2 O 5 , and ZrO 2 Including TiO 2 +P 2 O 5 + ZrO 2 The chemically strengthened microcrystalline glass according to claim 14, wherein the content of is 2 to 8 mol%.
Citation Information
Patent Citations
Crystallized glass of three-dimensional shape, chemically strengthened glass of three-dimensional shape, and method for producing crystallized glass of three-dimensional shape and chemically strengthened glass of three-dimensional shape
WO2019167850A1
Crystallized glass, chemically strengthened glass, and semiconductor substrate
WO2020161949A1
Method for producing chemically strengthened glass and chemically strengthened glass
WO2020261710A1